THE ROLE AND IMPORTANCE OF CORPORATE CONTRACTS IN THE FORMATION OF CORPORATE RELATIONS - Suyunova Xurshida (Zeta Repository, 2023)
This article includes the concept, importance and role of contracts, especially corporate contracts concluded between corporations and their participants in the formation of corporate relations, disputes over corporate contracts are discussed.